Features of cooperation between higher education institutions of Ukraine and Poland in the context of European integration - Гордійчук, Євгенія (Pedagogy of Higher and Secondary Education, 2014)
Gordiychuk T. S. Features of cooperation between higher education institutions of Ukraine and Poland in the context of European integration. The article deals with the trends of the Ukraine educational system development as a member of the Bologna Union under conditions of the European integration of education. The features of higher education in Poland are investigated and the importance of the practical use of progressive experience in professional education of the Ukraine is proved.